PERANCANGAN SISTEM INFORMASI JASA LAUNDRY (STUDI KASUS PADA DINARA LAUNDRY BATURAJA) - meilantika, dian (SISKOMTI: Jurnal Sistem Informasi Komputer dan Teknologi Informasi, 2021)
Dinara Laundry is a laundry business located in Bataraja city. The process on laundry services is still not optimal, recording that is still done manually causes the difficulty of tracing the status of laundry on customers. The number of types of services and service packages on laundry services makes cashier admins have to look for a record of the rates used so that the calculation of laundry services will feel slow and the possibility of miscalculation. In addition, tracing the amount of income earned in each month needs to be calculated manually from the beginning of the period to the end. In designing the information system in this study using the PHP programming language and using MySQL databases. This web-based system will be accessed locally. It is hoped that this system will help laundry services so that it can improve the plan to customers.